Efficacy and safety of venous thromboembolism prophylaxis with apixaban in major orthopedic surgery - Werth S; Halbritter K; Beyer-Westendorf J (Dove Medical Press, 2012)
Sebastian Werth, Kai Halbritter, Jan Beyer-WestendorfCenter for Vascular Medicine and Department of Medicine III, Division of Angiology, University Hospital “Carl Gustav Carus” Dresden, Dresden, GermanyAbstract: Over the last 15 years, low-molecular-weight heparins (LMWHs) have been accepted as the “gold standard” for pharmaceutical thromboprophylaxis in patients at high risk of venous thromboembolism (VTE) in most countries around the world. Patients undergoing major orthopedic surgery (MOS) represent a population with high risk of VTE, which may remain asymptomatic or become symptomatic as deep vein thrombosis or pulmonary embolism. Numerous trials have investigated LMWH thromboprophylaxis in this population and demonstrated high efficacy and safety of these substances. However, LMWHs have a number of disadvantages, which limit the acceptance of patients and physicians, especially in prolonged prophylaxis up to 35 days after MOS. Consequently, new oral anticoagulants (NOACs) were developed that are of synthetic origin and act as direct and very specific inhibitors of different factors in the coagulation cascade. The most developed NOACs are dabigatran, rivaroxaban, and apixaban, all of which are approved for thromboprophylaxis in MOS in a number of countries around the world. This review is focused on the pharmacological characteristics of apixaban in comparison with other NOACs, on the impact of NOAC on VTE prophylaxis in daily care, and on the management of specific situations such as bleeding complications during NOAC therapy.Keywords: major orthopedic surgery, apixaban, dabigatran, edoxaban, rivaroxaban, deep vein thrombosis, venous thromboembolism, VTE prophylaxis